Simplify: (x – 4)(x2 – 3x – 9)
A x3 + x2 – 3x – 36
B x3 – 7x2 – 21x + 36
C x3 – 7x2 + 3x + 36
D x3 – 4x2 – 12x + 36

Respuesta :

Hi there!

(x - 4) (x² - 3x - 9)

⇒ (x³ - 3x² - 9x) + (- 4x² + 12x + 36)

⇒ x³ - 3x² - 9x - 4x² + 12x + 36

⇒ x³ - 7x² + 3x + 36

Hence,
[tex]\textbf{Option \:C.}[/tex] x³ - 7x² + 3x + 36 is Correct.

~ Hope it helps!
iCarl
[tex]\sf Hello![/tex]

[tex]\sf (x - 4).(x^{2} - 3x - 9)[/tex]

⇒ [tex]\sf x^{3} - 3x^{2} - 9x - 4x^{2} + 12x + 36[/tex]

⇒ [tex]\sf x^{3} - 3x^{2} - 4x^{2} - 9x + 12x + 36[/tex]

⇒ [tex]\sf x^{3} - 7x^{2} + 3x + 36[/tex]

[tex]\sf Hence,[/tex]

[tex]\sf C.\: \sf x^{3} - 7x^{2} + 3x + 36 \:is \:the \:required \:simplified\: form.[/tex]

~ [tex]\sf iCarl[/tex]
ACCESS MORE